传统相声的现代转化 ：以苗阜和王声的相声为例 = Modern transformation of traditional cross-talk (Xiangsheng) : take Miao Fu and Wang Sheng as a case study - 张亚坤 Zhang, Yakun (2016)
相声在中国民间说唱艺术中占据举足轻轻重的地位，但是随着时代的发展逐渐的被边缘化，进入了低谷期。就在相声渐渐被观众淡忘时，一个在地方台播出的相声却一夜之间爆红，席卷了大江南北相声爱好者的注意力，那就是陕西西安青曲社的相声演员苗阜和王声的原创相声——《满腹经纶》。苗阜和王声共同创作了上百段的相声，个人风格浓厚，有不少作品深受观众喜爱。在相声行业低迷的今天，苗阜和王声的崛起似乎给相声界带来了一股春风，让不少人因为他二人而对相声重新拾起了信心。本文对苗阜和王声二人的相声从文本创作到表演风格进行多方面的研究，通过对二人相声中西北元素的研究，探讨二人对于西北相声的继承与创新对他们的相声创作造成的影响； 其次通过对经典案例的分析对比，探讨相声在进行现代转化时所面临的挑战；最后通过对二人相声艺术的反思找出二人的优秀与不足之处，从而进一步探讨苗阜和王声是否能对相声的未来发展做出贡献以及是否还有进步的空间。Crosstalk is a comic folk art, pivotal in the Chinese cultural scene. With the development of media diversity, people have opted for entertainment alternatives, dimming the lustre of traditional Crosstalk. Furthermore, the lack of good scripts and competent actors have deemed Crosstalk industry to a standstill. This situation persisted until the broadcast of Miao Fu and Wang Sheng’s masterpiece, Man Fu Jing Lun, aired by a local television station. Indeed, Miao Fu and Wang Sheng’s co-authored scripts were not only works that exhibited their unique personalities, but also works that resonated with the people. The duo’s appearance offered Crosstalk performance a spring breeze, generating a buzz over Crosstalk in China. Hence this paper aims to review the works of Miao Fu and Wang Sheng by analyzing their works from script creation to stage performance. Furthermore, it hopes to find out to what extent the success of the duo would help shape and revitalise the traditional cultural art, and how rebranding Crosstalk would meet the aesthetic likes of the present demographics, thereby achieving the purpose of entertaining its viewers, young and old alike.